The Application of Group Counselling Guidance As An Effort To Shape Children's Morals In Batang Arah Nagari Tapan: Penerapan Bimbingan Konseling Kelompok Sebagai Upaya Pembentukan Moral Anak-anak di Nagari Batang Arah Tapan - Cahyu Annisa; Ahmad Khairul Nuzuli; Winda Oktaviana (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
Based on the implementation of community service activities in Nagari Batang Arah Tapan with a focus on building children's morals through Group Counseling Guidance Services, the results show significant success. Through an interactive process in groups.15 children managed to gain a deep understanding of good behavior and morals in society. Previously, they had not fully adopted a positive attitude, but through discussion and evaluation of social phenomena, they were able to develop a better understanding of everyday moral values. Children's positive response to the material and their collective commitment to implementing this learning into action indicates the potential for a sustainable positive impact in promoting good morals and behavior in their community. Thus, this activity provides real benefits in shaping children's morale and encouraging the adoption of positive values in everyday life in a sustainable manner